The inevitable role of human in CRM success: digging deep the human CSFs - Jan, Muhammad Tahir (JM Publishers, 2011)

(untitled)
The main purpose of this paper is to enhance the CRM literature through the development of a conceptual model highlighting the impact of human related CSFs on CRM success. A qualitative methodology has been used by extensively reviewing the extant literature on the topic. Evidences suggest that CRM can be successful when a company successfully retain the customers; however, for customer retention customer satisfaction is necessary. Both customer satisfaction and retention are possible by efficiently aligning different CSFs related to CRM. Literature confirms that CSFs related to human are vital if a company wants to reap the benefits of CRM. The present paper, therefore, extracted those human CSFs which positively impact CRM success and more importantly customer satisfaction. It also complements the recent research that has been conducted on exploring the role of human CSFs in CRM success. Finally, a model has been proposed for future testing.